Real World Fuel Consumption and Emissions From LDVs and HDVs - Weller, Konstantin; Lipp, Silke; Röck, Martin; Matzer, Claus; Bittermann, Andreas; Hausberger, Stefan (Frontiers in Mechanical Engineering, 2019)
Real world emission and energy consumption behavior from vehicles is a key element for meeting air quality and greenhouse gas (GHG) targets for any country. While CO2 fleet targets for vehicles are defined on basis of standardized test procedures, in real driving conditions manifold parameters show large variabilities. Main differences are Driving cycle Vehicle loading and driving resistances Ambient temperature levels, start conditions and trip length Gear shift behavior of the drivers Power demand from auxiliaries Fuel quality For the upcoming update of the Handbook Emission Factors for Road Transport (HBEFA 4.1) we have performed analysis, measurements and simulations to elaborate real world energy consumption values for 2-wheelers, passenger cars (PC), light commercial vehicles (LCVs) and heavy duty vehicles (HDVs), so called emission factors (EF). EFs show fuel consumption or emission level in [g/km] and [#/km] for fuel, gaseous exhaust gas components and also for the particle number (PN). EFs are provided for a lot of different traffic situations covering stop & go up to highway for different road gradient categories. EFs are different for each vehicle category and for each powertrain technology and emission standard (from EURO 0 gasoline PC to EURO VI HDV with CNG engine). To produce the EFs, vehicle tests from chassis dyno and from on-board measurements were collected in all European labs to set up models for all vehicle segments in the passenger cars and heavy duty emission model (PHEM). The models for PC and LCVs were based on weight and road load data available from the type approval test, the worldwide harmonized light vehicles test procedure (WLTP), and then calibrated in a stepwise approach to consider all influences in real world driving. Finally, the results for new vehicle fleet fuel consumption values were compared with data from the fuel consumption monitoring data base. For HDVs, the models are based on data from the development of the HDV CO2 determination method (Regulation (EU) 2017/2400, “VECTO”). The methods and also the results in terms of differences between real world and type approval for loading, road load, energy consumption and emission levels are described in this paper.